Comprehensive analysis of nutritional and antioxidant properties of Cucumis callosus peel - Chaudhary, Priyanka; Gupta, Kalpana (Current Botany, 2025)
Cucumis callosus (commonly known as Kacheri) fruit is typically analyzed for its nutritional components, including moisture, ash, protein, fat, fibre, and carbohydrates. However, specific studies on C. callosus remain limited. Peel of C. callosus is a rich source of nutrients and analyzing the bioactive composition reveals its potential benefits. It constitutes about 20% of the total residue and is often considered an environmental challenge due to disposal issues. In this study, the phytochemical and proximate compositions of C. callosus peels were analyzed. The proximate analysis revealed a fat content of 6.89%, protein content of 9.34%, moisture content of 9.59%, ash content of 8.18%, and carbohydrate content of 36.66%. The crude fibre in the peels was found to be 29.34±0.94%. The crude fibre C. callosus content of peels was significantly higher compared to other vegetable peels. C. callosus has demonstrated remarkable functional properties, exhibiting a water-holding capacity 26 times its own weight and an oil-holding capacity 16 times its own weight. The methanolic extract of C. callosus peel exhibited antioxidant activity with an IC50 value of 67.76±2.34 μg/mL in the DPPH assay, indicating its potential as a promising natural antioxidant source. The mineral analysis result shows Iron as a major element followed by zinc and copper, and manganese highlighting their potential nutritional benefits. This study aims to raise awareness about the potential of C. callosus peels as a valuable source of phenolic compounds and iron element. The research underscores the importance of utilizing these peels in various food products to enhance their nutritional and technological properties.